Indole-3-propionic acid alleviates chondrocytes inflammation and osteoarthritis via the AhR/NF-κB axis - Huangming Zhuang; Xunshan Ren; Fuze Jiang; Panghu Zhou (BMC, 2023)
Abstract Background Osteoarthritis (OA) is a common chronic disease characterized by chronic inflammation and extracellular matrix degradation. Indole-3-propionic acid (IPA) is a tryptophan metabolite secreted by intestinal flora, which can exert anti-inflammatory effects in a variety of diseases. In this study, we further investigated the potential therapeutic role of IPA in OA and the underlying mechanism. Methods IL-1β was utilized to induce chondrocyte inflammation. Then, the cytotoxicity of IPA on rat chondrocytes was assessed. Meanwhile, RT-qPCR, Griess reaction, ELISA, Western blot and immunofluorescence were performed to evaluate the expression of inflammatory factors and stromal proteins, and the NF-κB pathway in chondrocytes treated with IL-1β alone, with IPA or with aryl hydrocarbon receptor (AhR) knockdown. An OA rat model was established by anterior cruciate ligament transection, and hematoxylin-eosin staining, Safranin-O/Fast Green staining and immunochemistry were applied to estimate OA severity. Results IPA did not affect cellular viability at concentrations up to 80 µM. IPA significantly inhibited the IL-1β-induced expression of inflammatory factors (Nitric oxide, PGE2, TNF-α, IL-6, iNOS and COX-2) and matrix-degrading enzymes (MMP-3, MMP-13 and ADAMTS-5), upregulated the expression of anabolic markers (aggrecan and collagen-II) and inactivated the NF-κB pathway. However, AhR knockdown could abolish the above protection capabilities and the suppression of the NF-κB pathway induced by IPA. Furthermore, IPA significantly reduced serum inflammatory cytokines expression, cartilage destruction and synovitis in vivo, demonstrating its protective role in OA progression. Conclusion IPA improved IL-1β-induced chondrocyte inflammation and extracellular matrix degradation through the AhR/NF-κB axis, which provides an innovative therapeutic strategy for OA.